The Degree to which the Leaders of Public Schools in Riyadh City Practice Toxic Leadership and its Relationship to the Level of Psychological Well-being of Teachers from their Perspectives - Al-Dosari, Sharea Bin Ayedh; Al-Rashidi, Anwar bint Hamad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to reveal the degree of public-school leaders ’practice in Riyadh city of toxic leadership, the level of psychological well-being and the relationship of the two variables with each other from the teachers’ point of view in those schools. The researchers used the descriptive survey approach, a questionnaire designed by researchers consisting of (45) items distributed on two axes, and it was applied to a random sample of (252) teachers. The results showed that the degree of school leaders ’practice of toxic leadership obtained an overall average of (1.60 out of 5). That is, with a (low) rating, and that the level of psychological well-being obtained an overall average of (3.40 out of 5), that is, a (high) rating. It also revealed the existence of a statistically significant positive relationship between toxic leadership and psychological well-being, reaching 0.15 and indicating a very weak relationship, With no statistically significant differences in the strength of the correlational relationship due to the effect of gender, experience, or educational stage. Based on the results, the researchers presented a set of recommendations and proposals to prevent toxic leadership and maintain a high level of psychological well-being among teachers.